Reasons for Japan's low unemployment rate - Uwe Vollmer (Intereconomics, 1988)
Since the beginning of the seventies, most OECD member countries have suffered from a substantial increase in measured unemployment rates. A notable exception is Japan, whose official unemployment rate is far below observed figures in other countries. This article examines the reasons why Japan's unemployment record has been better than those of the USA and West Germany.
Keywords: 330